POLA PEMBINAAN KADER KOMUNITAS SAHABAT MUDA DALAM MENCETAK YOUNG SOCIAL LEADER BERBASIS SOCIAL ENTREPRENEURSHIP - Muhammad Thohir; Widatul Luthfiyah; Frisca Rachmadani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
Amil Zakat Institute as a da'wah institution has a very important role in empowering the Islamic community, including young people. The perception of young people, especially college students, as agents of change seems to have been eroded by the fact that unemployment of undergraduate graduates has increased. This problem, of course, begins with a lack of understanding by young people about real-life turmoil, resulting in them not trying to train skills or learn competencies that will be useful for life after becoming graduates. This study aims to describe the pattern of guidance based on Social Entrepreneurship carried out by the Sahabat Muda Community LagzisPeduli Foundation in overcoming the problem of youth unemployment in three ways; look at the program, strategy, and implications. The method used is descriptive qualitative, with data collection techniques using interviews, observation, and documentation. The results obtained by SahabatMuda have succeeded in producing Young Social Leaders when the cadres have completed training. Social Entrepreneurship basis with three indicators carried by Sahabat Muda Community have proven to be successful in producing Young Social Leaders.